APPLICATION OF STAD MODELS TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS X IPA HIGH SCHOOL OF MATHEMATICS ON COMPOSITION OF FUNCTION AND INVERSE FUNCTION - Febia Rimasuita (Peneliti.net, 2019)
The purpose of the study was to determine whether the application of the Student Team Achievement Division (STAD) Cooperative Learning Model could improve student learning outcomes in mathematics and to find out how much an increase in student learning outcomes in mathematics about the composition of inverse functions and functions after using the Cooperative Learning Model Type Student Achievement Division (STAD) in class X IPA ,SMAN 1 Tajur Halang Bogor. The research method used in this research is analytic descriptive through classroom action research that is a study used to collect data, describe, process, analyze, conclude and interpret data so as to obtain a systematic picture. Descriptive research methods of analysis are used to find out the problem by describing in detail and clearly, as well as conducting a data analysis of the problem to obtain a conclusion with the aim of systematically describing and analyzing a factual fact.The use of cooperative learning model type student team achievement division (STAD) can be a fun learning variation for students so that it is proven to improve student learning outcomes. The magnitude of the increase in student outcomes as follows when the pre-cycle average value of 63.89 then in cycle 1 an increase to 75.14 and in cycle 2 to 83.61.